1979
DOI: 10.1037/0278-7393.5.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Two models of recognition memory: A test.

Abstract: Predictions from lexical-marking theory and a scanning model of recognition memory were compared in a continuous-recognition paradigm. The results were at least consistent with the scanning model and in two cases were at odds with lexical-marking theory. In particular, the probability of making a false-recognition error to the synonym of a previously presented word remained constant over a lag of 120, whereas a recognition-control condition showed a large decrement. Lexical-marking theory predicts equal decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This outcome replicates the standard false-recognition effect first reported by Underwood (1965). The false-recognition rate for weakly related lures was greater than obtained in many prior studies (e.g., L. M. Paul, 1979), and the rate for the critical nonpresented words was dramatically larger than the rate for the weakly related words. As shown in Table 1, the false-alarm rate for the critical nonstudied lures (.84) approached the hit rate (.86), r(35) < 1,SEM =.036,™.…”
Section: Output Quintilesupporting
confidence: 86%
See 1 more Smart Citation
“…This outcome replicates the standard false-recognition effect first reported by Underwood (1965). The false-recognition rate for weakly related lures was greater than obtained in many prior studies (e.g., L. M. Paul, 1979), and the rate for the critical nonpresented words was dramatically larger than the rate for the weakly related words. As shown in Table 1, the false-alarm rate for the critical nonstudied lures (.84) approached the hit rate (.86), r(35) < 1,SEM =.036,™.…”
Section: Output Quintilesupporting
confidence: 86%
“…Although there have been a few reports of robust false recognition effects (Hintzman, 1988), in many experiments the false recognition effect was either rather small or did not occur at all. For example, in a study by L. M. Paul (1979), in which synonyms were presented at various lags along with other, unrelated lures, the false recognition effect was only 3% (a 20% false-alarm rate for synonyms and a 17% rate for unrelated lures). Gillund and Shiffrin (1984) failed to find any false recognition effect for semantically related lures in a similar paradigm.…”
mentioning
confidence: 99%
“…After a seminal paper published by Roediger and McDermott 2 , interest of false memory research skyrocketed (see 7 ), resulting in over 2,800 citations of that article to date. According to Roediger and McDermott, they revived the experimental design created by Deese because there was no reliable laboratory paradigm to induce false recall, while evidence of false recognition (e.g., 8,9 ) did "little to discourage the belief that more natural, coherent materials are needed to demonstrate powerful false memory effects" 2 .…”
Section: Introductionmentioning
confidence: 99%
“…He showed that these pairedassociate distractors were often falsely recognized at test. However, in many paired-associate false-memory studies, the falserecognition effect was small or not found at all (e.g., Gillund & Shiffrin, 1984;Paul, 1979).…”
mentioning
confidence: 99%